The Design and Construction of a Self Amplified Loud Speaker. - Tumuhamye Ronald (Kabale University, 2023)
The self-amplified loud speaker was designed with three parts: pre-amplifier unit, tonality control unit and power amplifier unit. For the pre-amplifier unit, Tl071CP integrated operational amplifier is used to achieve the gain of 4; for the tonality control unit, a filter is designed to achieve different tone; for the power amplifier unit, LM386N-1 integrated low voltage power amplifier is applied. The self-amplified loud speaker was not constructed because the LM386N-1 integrated low voltage power amplifier is not available in market